How does EU cohesion policy work? Evaluating its effects on fiscal outcome variables - Tobias Hagen; Philipp Mohl (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
The impact of EU Cohesion Policy has mainly been evaluated with regard to its growth effects. We extend the perspective by investigating the impact of EU Cohesion Policy on public investments and budget deficits in order to learn more about the channels through which this policy field works. Using a dataset of 27 EU countries for the time period 1982-2006, we find that EU Cohesion Policy payments do not cause public investments to increase significantly, which points to a crowding out of national investment. Moreover, the hypothesis that EU Cohesion Policy is used for the consolidation of public budgets cannot be completely rejected.
Keywords: C23; H54; H62; 330; EU Cohesion Policy; public investment; public deficits; panel data